(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This article has no abstract. The first 100 words appear below: A 18-year-old boy came with the complaints of mild pain during mastication on the lower right posterior tooth for two weeks. He gave the history of severe pain on offending tooth one month before, which subsided within a few days after taking medication from a local pharmacy. On clinical examination, a deep occlusal caries was present on the lower right first molar tooth. The tooth was tender to the vertical percussion but not associated with any swelling or discharge. The vitality test revealed that the tooth was non-vital.